2015
DOI: 10.1002/14651858.cd007951.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis for lithium poisoning

Abstract: BackgroundLithium salts, particularly lithium carbonate, are frequently used to treat bipolar disorder and mania. Lithium poisoning, which can occur as a result of reduced renal elimination, prescribing error, drug-drug interactions, or deliberate overdosage, produces neurologic injury that can be permanent. Hemodialysis is o en recommended to treat lithium poisoning. Although hemodialysis clearly enhances the elimination of lithium, it is unclear whether this translates into improved patient outcomes. Evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…Although no robust evidence from clinical trial has been reported so far, several clinical reviews have described the rationale of RRT for lithium poisoning according to the serum lithium concentration; the threshold is 4.0–5.0 mEq/L for acute poisoning and 2.5 mEq/L for chronic poisoning. However, no clear cut‐off value and standard therapy for acute‐on‐chronic poisoning has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Although no robust evidence from clinical trial has been reported so far, several clinical reviews have described the rationale of RRT for lithium poisoning according to the serum lithium concentration; the threshold is 4.0–5.0 mEq/L for acute poisoning and 2.5 mEq/L for chronic poisoning. However, no clear cut‐off value and standard therapy for acute‐on‐chronic poisoning has been established.…”
Section: Introductionmentioning
confidence: 99%
“…no protein binding, limited volume of distribution, absence of metabolism, and exclusive renal elimination), extracorporeal toxin removal (ECTR) represents the method of choice for enhancing lithium elimination in poisoning, if lithium elimination is compromised despite optimal fluid management . However, ECTR indications and benefits in lithium poisoning are still controversial …”
Section: Introductionmentioning
confidence: 99%
“…1 However, ECTR indications and benefits in lithium poisoning are still controversial. [2][3][4][5] The EXtracorporeal TReatments In Poisoning (EXTRIP) workgroup, an international workgroup including clinical toxicologists, nephrologists, epidemiologists and pharmacologists, 6 provided recommendations on ECTR use in lithium poisoning, based on a systematic literature review and considered to date as the most up-to-date international guideline. 1 Using the GRADE system, all recommendations were grade D (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Though Cochrane correctly concluded that there are no randomized controlled human trials to inform the decision to perform haemodialysis in lithium-poisoned patients, their focused methodology prevented them for offering any clinical decision support. 10 In contrast, the Extracorporeal Treatments In Poisoning (EXTRIP) workgroup (https://www.extrip-workgroup.org) assembled a multidisciplinary team of international experts (including toxicologists, pharmacologists, nephrologists, intensivists, and methodologists) who reviewed the entirety of the existing literature and used a sound, transparent, and reproducible evidence and consensus-based methodology to offer their best recommendations for ECTR in lithium-poisoned patients. 11 Despite achieving consensus on many items, the low level of available evidence created the significant likelihood of imprecision around the clinical conditions and laboratory values used as criteria to either suggest or recommend ECTR for a given patient.…”
mentioning
confidence: 99%